On the Origin of Iron Age Phoenician Ceramics at Kommos, Crete: Regional and Diachronic Perspectives across the Bronze Age to Iron Age Transition - Gilboa, Ayelet (Bulletin of ASOR, 2015)
Excavations at Kommos, Crete, have unearthed hundreds of fragments of Iron Age Levantine transport jars--an unusual phenomenon in the Iron Age Mediterranean. Though usually termed "Phoenician," their origin has never been demonstrated by fabric analysis. This article presents such an analysis, employing petrography and chemistry. To a large extent, this is a rather unexplored domain because fabric analyses of Phoenician Iron Age ceramics overseas are surprisingly few. The compositional data indicate that most of the jars are indeed from Lebanon, specifically from its southern coast. To place these results in a diachronic and regional perspective, we discuss the chronology of these finds and then compare the production centers identified with those defined in other provenance studies of Levantine containers overseas. This illustrates the growing importance of southern Lebanese polities in Iron Age Mediterranean networks at the expense of the Syrian littoral, on the one hand, and the coast of the southern Levant, on the other.